2008
DOI: 10.1002/j.1556-6678.2008.tb00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Classism, Ableism, and Heterosexism in Counselor Education

Abstract: As the counseling profession charts its future course, issues related to classism, ableism, and heterosexism remain fully incorporated within the multicultural/social justice curriculum. The authors define each of these forms of oppression, explicate their intersections with race, and summarize the resulting implications for counseling education and training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 37 publications
2
55
0
1
Order By: Relevance
“…Furthermore, many participants conceptualized disability from a medical model and deficit perspective. This finding supports the work of Smith et al (), who found that counselor trainees internalize pathologizing views of disability based upon their socialization in a culture that endorses such a view. Participants expressed awareness that they were perpetuating the deficit‐oriented views of disability by not being critical and not engaging in social advocacy.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, many participants conceptualized disability from a medical model and deficit perspective. This finding supports the work of Smith et al (), who found that counselor trainees internalize pathologizing views of disability based upon their socialization in a culture that endorses such a view. Participants expressed awareness that they were perpetuating the deficit‐oriented views of disability by not being critical and not engaging in social advocacy.…”
Section: Discussionsupporting
confidence: 89%
“…The internalizing of these discourses leads to under‐ and overvaluing of self and others and discrimination based on perceived social class status. Counselors and family therapists in training are not exempt from classist views and must critique their own biases as part of self‐of‐the‐therapist development (Smith et al., 2008).…”
Section: Classismmentioning
confidence: 99%
“…Over the past two decades, family therapy training programs have increasingly attended to student diversity (McDowell, Fang, Brownlee, Gomez Young, & Khanna, 2002; McDowell, Storm, & York, 2007), often highlighting gender (Brody, 1990), sexual orientation (Green, 2004), nation of origin (McDowell et al., 2006), and race (McDowell, 2004). There remains, however, only cursory inclusion of social class in family therapy, psychology, or counselor education programs (Ballinger & Wright, 2007; Langhout, Rosselli, & Feinstein, 2007; Smith, Foley, & Chaney, 2008). There is likewise a dearth of research exploring social class and classism as a self‐of‐the‐therapist issue in family therapy training.…”
mentioning
confidence: 99%
“…Individuals might hold negative attitudes, beliefs, or assumptions about people or groups of people on the basis of their social class or SES standing (L. Smith, ; L. Smith, Foley, & Chaney, ). Collins and Yeskel () argued that such evaluations of one's character are a form of classism.…”
Section: Definitions Of Termsmentioning
confidence: 99%